Patents, Transaction Costs and Academic Research Project Choice1. Issue 289 (19th December 2013) - Jensen, Paul H.; Webster, Elizabeth
<x xml:space="preserve">Abstract</x> Survey data from over 3, 000 academic scientists show that nearly half of these scientists report that their choice of research projects has been affected (to some degree) by the presence of third‐party patents. Our evidence suggests that the operation of this patent‐induced effect is through (i) restrictions patent owners place on the timing of follow‐on publications and (ii) disincentives for open exchange of information between scientists. While the need to translate science into commercial use is potentially a valuable source of productivity growth, this should be balanced against the need for openness and information sharing in the scientific realm.